The Effect of the Realistic Mathematic Education (RME) Learning Model On Students’ Mathematical Problem Solving Abilities : A Meta-Analysis - Habib Ratu Perwira Negara; Malik Ibrahim; Kiki Riska Ayu Kurniawati; Anisa Firdaus; Risma Maulidina; Muhammad Saifudin (Justek : Jurnal Sains dan Teknologi, 2021)
Abstract: Realistic Mathematics Education (RME) learning is a learning approach that uses contextual issues and student-focused learning. This study aims to find out the huge influence of the Realistic Mathematics education learning model on students' mathematical problem-solving skills. The research method used is a meta-analysis with the help of JASP software by collecting data from the results of research indexed indexer databases such as Google Scholar, SINTA, and Garuda Portal. The data were taken in accordance with the criteria of inclusion and exclusion of this study to then be determined by the value of effect size (ES) and standard error (SE). The results of the data analysis using JASP software showed that realistic mathematics education (RME) learning model on mathematical problem-solving skills of students as a whole has a positive influence which is obtained by estimation (ES) of 0.71 or 71% based on RE Models with high category, as well as the p-value (egger's test) of 0.121 which means no publication is indicated bias, as well as the results of moderator variable analysis on classification per education level. This means that realistic Mathematics Education (RME) learning model for students' mathematical problem-solving skills can be said to be appropriate if used for students, especially in junior high and elementary school level.Abstrak: Pembelajaran Realistic Mathematic Education (RME) ini merupakan pendekatan pembelajaran yang menggunakan masalah kontekstual, dan pembelajaran terfokus pada siswa. Penelitian ini bertujuan untuk mengetahui besar pengaruh model pembelajaran Realistic Mathematic education terhadap kemampuan pemecahan masalah matematis siswa. Metode penelitian yang digunakan adalah meta-analisis dengan bantuan software JASP yaitu dengan cara  mengumpulkan data dari hasil-hasil penelitian yang terindeks database pengindeks seperti Google Scholar, SINTA, dan Portal Garuda. Data yang diambil sesuai kriteria inklusi dan ekslusi penelitian ini untuk kemudian ditentukan nilai effect size (ES) dan standard error (SE). Hasil analisis data menggunakan software JASP menunjukkan bahwa model pembelajaran Realistic Mathematics Education (RME) terhadap Kemampun Pemecahan Masalah Matematis Siswa secara keseluruhan pengaruhnya positif yang dimana di dapatan nilai Estimasi (ES) sebesar 0.71 atau 71% berdasarkan RE Models dengan kategori tinggi, serta nilai p-value (egger’s test) sebesar 0.121 yang berarti tidak terindikasi publication bias,begitu juga dengan hasil analisis variabel moderator pada klasifikasi per jenjang pendidikan. Ini berarti model pembelajaran Realistic Mahematics Education (RME) terhadap Kemampuan Pemecahan Masalah matematis Siswa bisa dikatakan sudah tepat jika digunakan untuk Peserta didik terutama pada jenjang SMP dan SD.